Impact of disturbance on population and genetic structure of tropical forest trees - R, Wickneswari; WS, Ho; KS, Lee; CT, Lee (ARBORA, 2004)
Effects of selective logging on the population and genetic structure of Shorea curtisii, Dryobalanops aromatica and Scaphium macropodum were examined via two approaches:(1) to investigate the immediate effects by studying a same population before and after logging and,(2) to determine the long term effects by comparing regenerated stands with an adjacent unlogged stand, assuming that they were genetically identical before logging. Reduction in basal area of trees from different size classes due to a single ...